ANALISIS MANOVA: STRATEGI GAME BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MINAT BELAJAR PESERTA DIDIK - Batin Saputra, Adi; Andriani, Siska; Risqa JL, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Game Based Learning strategy on students’ creative thinking and mathematical problem-solving skills in terms of their learning interest, using MANOVA analysis. The background of this research is based on the fact that students’ ability to solve mathematical problems creatively is still low, as well as the lack of learning variations that can actively enhance students’ learning interest. This study employs a quantitative approach with a Quasi-Experimental Design. The research subjects were seventh grade students at SMP Negeri 21 Bandar Lampung, consisting of an experimental class and a control class. Data analysis was conducted using two-way MANOVA with Pillai’s Trace test. The MANOVA analysis results show that the Game Based Learning strategy is effective in improving students' creative thinking and mathematical problem solving skills. Learning interest also has an effect; however, no significant interaction was found between the two, indicating that Game Based Learning is effective across all levels of learning interest.